STRATIGRAPHY AND SEDIMENTOLOGY OF THE BUG LOESS (PLEISTOCENE: UPPER VISTULIAN) BETWEEN KIEV AND ODESSA (UKRAINE) - Chlebowski R.; Gozhik P.; Lindner L.; łLanczont M.; Wojtanowicz J. (My University, 2003)
Documented type sections (Vyazivok, Stayky, Uman, Troitskoye, Altestovo, Roxolany and Lebedivka) provide a basis for Pleistocene stratigraphy between Kiev and Odessa, and have been used to characterise the heavy mineral composition and part of the light fraction of the Bug loess in this area. These sections document an almost complete succession of climatic change during the last 780 ka, worked out mostly using loesses and palaeosols though also in the case of the first two sections, of glacial deposits. The heavy mineral composition of the Bug loess in these sections documents five mineral groups on the basis of their resistance to weathering and susceptibility to deflation and aeolian transport. Radar charts with particular mineral groups indicate mineralogical and genetic trends in the loesses. Moreover, in some sections the light fraction of the loess investigated contains derived microfossils (mainly foraminifers) of Cretaceous age, indicating source areas for the loess-forming material, and constraining the palaeowind directions. The data obtained allow distinction of three accumulation zones of the Bug loess in this area, reflecting loesses derived from different source areas and transported by winds from different directions. In northern sections (zone A), the Bug loess was accumulated by winds blowing from the west and north-west. More to the south (zone C), the same loess was accumulated by winds from the east and south-east. Loess preserved in zone B, between these areas, could be accumulated by winds from either of these directions.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен